Capability of insulator study by photoemission electron microscopy at SPring‐8. (29th May 2013) - Ohkochi, Takuo; Kotsugi, Masato; Yamada, Keisuke; Kawano, Kenji; Horiba, Koji; Kitajima, Fumio; Oura, Masaki; Shiraki, Susumu; Hitosugi, Taro; Oshima, Masaharu; Ono, Teruo; Kinoshita, Toyohiko; et al.
<x xml:space="preserve">Abstract</x> The observation method of photoemission electron microscopy (PEEM) on insulating samples has been established in an extremely simple way. Surface conductivity is induced locally on an insulating surface by continuous radiation of soft X‐rays, and Au films close to the area of interest allow the accumulated charges on the insulated area to be released to ground level. Magnetic domain observations of a NiZn ferrite, local X‐ray absorption spectroscopy of sapphire, high‐resolution imaging of a poorly conducting Li0.9CoO2 film surface, and Au pattern evaporation on a fine rock particle are demonstrated. Using this technique, all users' experiments on poorly conducting samples have been performed successfully at the PEEM experimental station of SPring‐8.